Desain Media Pembelajaran Interaktif Mata Pelajaran IPA untuk Anak Tunagrahita Ringan Kelas VIII di SLB Amanah Bunda Sitapung Nagari Balai Gurah Kecamatan Ampek Angkek Agam - Elbazs, Qadisa Awdidia; Derta, Sarwo; Efriyanti , Liza; Khairuddin, Khairuddin (Indonesian Research Journal on Education, 2023)
Special schools (SLB) are special schools for children who have difficulty participating in learning either due to physical, emotional or mental disorders. At the Amanah Bunda Sitapung Special School (SLB) the problems found by researchers were that the learning media used were less varied which caused boredom while studying, because students were bored and the focus of students was also reduced, and there was no animated video-based learning media. From these problems, interactive learning media were designed for science subjects regarding growth and development in humans, especially the physical characteristics of boys and girls at puberty for Tugrahita children with the Tellagami application. The results of the design of interactive learning media in the form of videos. The manufacturing process starts from thecollection of materials, assembly, distribution, distribution, and finally product testing. The method used is the 4-D version of RnD development method which consists of: define, design, develop, desseminate with the Luther-Sutopo Multimedia development model. The results of Interactive learning media research on science subjects get an average validity test value of 0.80 with very valid criteria, practicalitytest an average value of 0.89 with very high criteria, and an effectiveness test an average value of 0.80 with criteria very effective. Based on the results of product testing, the science learning media for mentally retarded children using the Tellagami application is valid, practical, effective and can facilitate students in the learning process.